Effect of Gamma Radiation on Sterility, Sexual Competitiveness and Mating Ability of Carob Moth Ephestia calidella (Guen.)Irradiated as Pupae - T. R. Ahmad; B. Sh. Hamad; G. S. Barkhi (مجلة بغداد للعلوم)
When mature pupae (2 days before eclosion) of Ephestia calidella (Guen.) were irradiated with the doses of 0, 100, 200, 300 and 400 Gy, the males had a high level of sterility which was 92% at 300 Gy, but it was not significantly different from those treated with 200 and 400 Gy respectively. Furthermore,a high level of sterility (100%) was obtained for female pupae treated with 400 Gy. Meanwhile, when both males and females irradiated as pupae (2 days before eclosion) with 200, 300 and 400 Gy showed a high level of sterility which was 94.4, 98.2 and 99.6%, respectively. It is evident that females were less radio-resistant than males. When males from irradiated pupae at different doses added to untreated adult at ratio of (3:1:1) irradiated males :unirradiated males: unirradiated females the percentage of egg hatch decreased from 76.4% in the control to 36.3% at the dose of 400 Gy. However, sexual competitiveness value and inseminate female irradiated as pupae reduced with increasing doses.